Offenheit als Moment einer bildungstheoretischen Grundlegung pädagogischer Verantwortung in Organisationen. - Röseler, Christoph; Sausele-Bayer, Ines (Organisation und Verantwortung, 2020)

Organisationen als Orte gelebter (Inter-)Kulturalität - Neubauer, Manuel; Röseler, Christoph (Gruppe. Interaktion. Organisation., 2019)
This article deals with different perceptions of cultural diversity and their implications for practice in organisations. The retracing of a theoretical differentiation, namely the distinction between culture and collective, allows to distinguish between cultural standardisations and collective affiliations. Thereupon in using the concept of multicollectivity, a specific understanding of cultural diversity is developed. It comes without preconceived categorisations and offers the advantages of pointing out commonalities and promoting social cohesion. Finally the question will be discussed to which extent organisations, from a pedagogical perspective, represent a cultural practice and therefore can be understood as places, where culture is produced interactively.
CRIS-Team WoS Importer:2019-11-22

Tagungsbericht. Normativität in der Erziehungswissenschaft. - Röseler, Christoph (Zeitschrift für Soziologie der Erziehung und Sozialisation, 2017)